A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water. (January 2023) - Qiao, Yu-Ting; Lu, Ying-Xin; Yu, Peng-Fei; Feng, Nai-Xian; Li, Yan-Wen; Zhao, Hai-Ming; Cai, Quan-Ying; Xiang, Lei; Mo, Ce-Hui; Li, Qing X.
Abstract: Huge volumes of wastewater containing organic flotation reagents such as xanthates have been released into the environment via mining activities, greatly threatening the eco-environment safety. A simple and fast method is urgently needed for accurate analysis of various xanthates in mining and environmental water. Here, a robust method is realized for simultaneous determination of three trace xanthates (i.e., potassium ethyl xanthate, potassium butyl xanthate, and potassium isopropyl xanthate) in environmental water samples, including eutrophic water and flotation wastewater using solid phase extraction (SPE) and HPLC-MS/MS. HPLC-MS/MS parameters, SPE cartridges and eluting solvents, pH values, and SPE procedures were optimized. The new method had an excellent linearity in the range of 1–1000 μg/L (R 2 ≥ 0.998), low limits of detection (0.02–0.68 μg/L), and satisfactory accuracy and precision (72.9%–107.6% of average recoveries and <5% of relative standard deviations at 1, 10, 50, and 500 μg/L of xanthates). This is a first method developed for determination of trace xanthates in water samples. It was successfully applied to determine the target analytes in outdated flotation wastewater and river water samples, warranting the occurrence of trace xanthates (0.13–16.9 μg/L) in water and necessity of systematic investigation on environmental fate and risk of xanthates. Graphical abstract: Image 1 Highlights: The HPLC-MS/MS method is for the simultaneous analysis of three xanthates in water. WAX SPE cartridges concentrate and clean up the samples for xanthates analysis. The limits of detection are 10–10000 fold lower than those of the previous methods. Trace xanthates in water samples warrant further studies.